MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI BERMAIN KOLASE ANAK USIA 5-6 TAHUN KELOMPOK B DI TAMAN KANAK-KANAK PERGURUAN WAHIDIN BAGANSIAPIAPI - Rodiah, Rodiah; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Background behind in this study is less increased fine motor skills of children in the play collage, child's interest in seeing the shape, size and patterns of media collage and the lack of application of the collages play to help fine motor skills of children in kindergarten Universities Wahidin District of Bangko Rokan Hilir. How to improve the play collage of children aged 5-6 years in kindergarten College Wahidin Bagansiapiapi through fine motor skills. To find out how high the fine motor skills of children through the implementation of a collage play in group B TK College Wahidin Bagansiapiapi. This research is a classroom action research conducted in a cycle 2 each cycle consists of four phases: planning, action, observation, reflection, data collection tools used in this study is the observation sheet form. To determine the height increase fine motor skills through a collage Children in play fine motor children in kindergarten College Wahidin District of Bangko Rokan Hilir. This research is a classroom action research conducted in two cycles. In each cycle consists of four phases: planning, action, observation, reflection, data collection tools used in this study is the observation sheet form. The number of subjects in this study were 15 people. Data taken from the results of the evaluation at the end of each cycle. This study involved one colleague or another teacher as an observer. Based on data and results obtained percentage increase in the first cycle is 49.61% and increased to 70.44%, the second cycle can thus be concluded that the application of Collage playing in kindergarten Wahidin Rokan Hilir District of Bangko can increase fine motor skills of children in the age 5-6 years.Keyword: Fine Motor Skills, Play A Collage